2014
DOI: 10.1093/bja/aet375
|View full text |Cite
|
Sign up to set email alerts
|

Does the type of fluid affect rapidity of shock reversal in an anaesthetized-piglet model of near-fatal controlled haemorrhage? A randomized study

Abstract: Restoration of MAP was four times faster with HES than with LR in the early phase of controlled haemorrhagic shock. However, there was no evidence of increased vascular permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In an animal model of hemorrhagic shock, restoration of blood pressure was four times faster with hydroxyethyl starch (HES) than with LR (P \ 0.001) and required fourfold less volume (P = 0.04). 65 Avoidance of excess crystalloid is also the most important independent predictor of outcomes within an enhanced recovery protocol. 66 Although it is possible that a crystalloid could be used effectively for fluid challenges, this remains uncertain; therefore, in our opinion, a colloid is still the rational choice, especially if fluid challenges are given only in the context of blood loss and objective hypovolemia.…”
Section: Which Fluid Should I Use?mentioning
confidence: 99%
“…In an animal model of hemorrhagic shock, restoration of blood pressure was four times faster with hydroxyethyl starch (HES) than with LR (P \ 0.001) and required fourfold less volume (P = 0.04). 65 Avoidance of excess crystalloid is also the most important independent predictor of outcomes within an enhanced recovery protocol. 66 Although it is possible that a crystalloid could be used effectively for fluid challenges, this remains uncertain; therefore, in our opinion, a colloid is still the rational choice, especially if fluid challenges are given only in the context of blood loss and objective hypovolemia.…”
Section: Which Fluid Should I Use?mentioning
confidence: 99%
“…Ganter et al reported that VEGFs were not increased and their levels did not correlate with severity of injury and tissue hypoperfusion in the early stages after trauma [17]. In another animal study, fluid resuscitation with HES did not increase VEGF levels and hence, did not lead to capillary leakage [7]. Although prolonged hypoperfusion and hypoxia caused by hemorrhagic shock can induce inflammatory responses leading to enhanced vascular permeability and capillary leaks [18], earlier hemodynamic stability by fluid resuscitation with HES can attenuate the inflammatory responses [19,20].…”
Section: Fluid Resuscitation In Septic Shock or Hemorrhagic Shockmentioning
confidence: 94%
“…Colloids have been shown to maintain intravascular volume and hemodynamics better than crystalloids through preservation of colloid osmotic pressure [4,5]. Several studies have demonstrated that fluid resuscitation with colloids compared to crystalloids might improve the outcomes of acute hemorrhagic shock [6,7]. Moreover, recent studies have elucidated the detailed effects of fluid resuscitation with hydroxyethyl starch (HES) on microcirculation and micro-vessels in subjects with acute hemorrhagic shock [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…30 A recent, carefully controlled study of hemorrhagic resuscitation in piglets clearly demonstrated that in acute hypovolemia, HES is four to five times more effective than crystalloids in terms of both volume and rapidity of resuscitation. 31 It should be noted that not all HES restores blood volume equally after hemorrhage. In normal volunteers, a tetrastarch restored blood volume better than did a hetastarch.…”
Section: Trauma and Acute Hypovolemiamentioning
confidence: 99%